Recent advanced in surface guided radiation therapy - Freislederer, Philipp; Kügele, M.; Öllers, M.; Swinnen, A.; Sauer, T.-O.; Bert, C.; Giantsoudi, D.; Corradini, S.; Batista, Vania (Radiation oncology, 2020)
The growing acceptance and recognition of Surface Guided Radiation Therapy (SGRT) as a promising imaging technique has supported its recent spread in a large number of radiation oncology facilities. Although this technology is not new, many aspects of it have only recently been exploited. This review focuses on the latest SGRT developments, both in the field of general clinical applications and special techniques.